A correlational study of achievement motivation and pupil's performance in the standard five assessment examination from selected schools in Selangor - Elias, Habibah (1978)
The purpose of this study was to examine whether there was any significant correlation between pupils performance in the Standard Five Assessment Examination in relation to a number of variables namely, achievement motivation, socio-economic status, intelligence, area of residence, school milieu and parental encouragement. The main null hypothesis tested was: "That there was no significant correlation between performance in the Standard Five Assessment Examination in relation to the following variables namely, the TAT, the questionnaire on motivation, the Children Achievement Scale, socio-economic status, intelligence, area of residence, school milieu and parental encouragement." Ninety pupils from forty English medium primary schools In Selangor, were selected from the 1973 Standard Five Assessment Examina tion Results through stratified random sampling and were divided into the successful group and the unsuccessful group which represented the three ethnic groups namely, the Chinese, Malays and Indians. Data were collected by means of individual interview. An intelligence test (Raven's Standard Progressive Matrices) was administered and three measures of achievement motivation were used namely, the Thematic Apperception Test, the Children Achieveme nt Scale and a questionnaire prepared by the researcher. In addition, a questionnaire was also prepared for the principals of schools, to get information regarding the school milieu. The data were analysed by means of Pearson's product moment correlation and analysis of varian In the correlation analysis, it was found that with the exception of the Children Achievement Scale and area of residence, all the other variables namely the TAT, questionnaire on motivation, socio-economic status, intelligence, school milieu and parental encouragement showed significant correlations (p <.01) with performance in the above examination. The TAT was found to have a high correlative value (p<.01) with a number of variables under study with the exception of the CAS and area of residence. The CAS as a measure of achievement motive showed negative correlations with all the variables under study. Socio-economic status was found to have significant correlations (p<.01) with several variables including performance in the above examination, the TAT, questionn aire on motivation, intelligence and parental encouragement. Another interesting finding was the significant correlation (p<.01) between parental encouragement in relation to performance in the examination, TAT, questionnaire on motivation, socio-economic status and intelligence.